Potential of Wild Yeast from Banana to Control Colletotrichum musae Fungi Caused Anthracnose Disease and Its Short Antagonistic Mechanism Assay - Anton Muhibuddin; Antok Wahyu Sektiono; Dewi Maratus Sholihah (Journal of Tropical Life Science, 2019)
Anthracnose caused by Colletotrichum musae is one of several important disease in banana fruit. An effective, cheap, and safe control method are necessary as a postharvest disease control alternative. This research aimed to obtain and identify wild yeast from banana which was isolated from its peel that has antagonist ability effectively in controlling anthracnose disease of banana fruit. Â This research was started with an isolation of C. musae and yeast from banana, followed by in vivo assay with count percentage antagonist level, slide culture, and in vivo assay to know pathogen incubation stage and incident disease level. The yeast that isolated from ambon variety was Candida sp. and Pichia sp. Metchnikowia sp. from kepok variety respectively.